2020
DOI: 10.3390/su12041404
|View full text |Cite
|
Sign up to set email alerts
|

Application of Reliability Analysis for Risk Ranking in a Levee Reconstruction Project

Abstract: Levees are embankments designed for passive flood protection. In order to reduce the potential of climate-induced flooding risks, it is necessary to reconstruct or upgrade the existing levees. Flood risk management aims to reduce the probability of floods and their potential adverse effects on the population, economy, and environment. This paper presents the novel application of reliability analysis for risk ranking in the Otok Virje-Brezje levee reconstruction project in the Republic of Croatia. To identify, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In a levee construction or reconstruction project, many kinds of source of risk could be involved. Kovačević et al (2020) [15] identified five key risks in a levee reconstruction project including (1) inadequate site investigation;…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a levee construction or reconstruction project, many kinds of source of risk could be involved. Kovačević et al (2020) [15] identified five key risks in a levee reconstruction project including (1) inadequate site investigation;…”
Section: Methodsmentioning
confidence: 99%
“…In a levee construction or reconstruction project, many kinds of source of risk could be involved. Kovačević et al (2020) [15] identified five key risks in a levee reconstruction project including (1) inadequate site investigation; (2) overtopping; (3) insufficiently detailed reconstruction design; (4) unsatisfactory performance of reconstruction works; (5) inaccurate monitoring and condition evaluation. Among these risks, this study focused on the risk of overtopping which occurs when water level exceeds the levee crest.…”
Section: Introductionmentioning
confidence: 99%
“…ANP replaces hierarchical structures with networks [158] by computing the independence between complex decision elements and offers all the benefits of AHP, including simplicity, flexibility, and the opportunity to review consistency in judgments [159]. Interaction is enabled between members of the same cluster (inner dependence) and elements of separate clusters (external dependence) [160]. With the interconnectedness of network elements, complex real-world situations can be modelled accurately [160].…”
Section: Analytical Network Process (Anp)mentioning
confidence: 99%
“…Interaction is enabled between members of the same cluster (inner dependence) and elements of separate clusters (external dependence) [160]. With the interconnectedness of network elements, complex real-world situations can be modelled accurately [160]. However, the hierarchical analysis assumes that higher levels are independent of lower levels, and in many decision-making processes, decision variables cannot be modelled hierarchically and independently unless combined hence the introduction of ANP [161].…”
Section: Analytical Network Process (Anp)mentioning
confidence: 99%
“…Fedorova et al [93] revealed that the social dimension of sustainability improves the management of conflicts related to the use of resources and social risks across the supply chain. Kovačević et al [94] calculated the reliability of risks ranking in levees for controlling floods in a non-PPP Croatian case study to prioritize the investment.…”
Section: Risk Management and Risk Allocationmentioning
confidence: 99%